Genetic risk for schizophrenia modulates WIN 55,212-2 reward: Evidence from a heterozygous transmembrane domain neuregulin 1 mutant mouse model - Rose Chesworth; Georgia Watt; Jaime Howard; Georgina Ding; Tim Karl (Psychopharmacology, 2026)
Background Cannabis abuse rates are up to ten times higher in individuals with schizophrenia than the general population, but it is unclear what is driving this high level of comorbidity. Genetic predisposition for schizophrenia may increase the risk of cannabis abuse; however, there is limited empirical support for this. Methods We investigated this question using a well-established genetic mouse model of schizophrenia risk, the heterozygous transmembrane domain neuregulin 1 mutant ( Nrg1 TM HET) mouse, which also shows behavioural and neural susceptibility to cannabis components. WIN 55,212-2 (WIN), a cannabinoid 1 (CB1) receptor agonist, was used to model the rewarding and aversive properties of cannabis. We first validated a conditioned place preference protocol to determine rewarding and aversive doses of WIN administration in C57BL/6J mice, the background strain of our schizophrenia mouse model. We then investigated the effects of these WIN dose regimes on place preference and locomotion in male and female Nrg1 TM HET mice and their control wildtype-like littermates. Results We found that low dose WIN (0.1 mg/kg) was rewarding in wildtype-like, but not in Nrg1 TM HET mice of both sexes. Conversely, male and female mice of both genotypes found high dose WIN (3 mg/kg) aversive. While all mice showed a similar locomotor response to low dose WIN administration, male Nrg1 TM HET mice showed an earlier development of locomotor tolerance to high dose WIN, with no differences in WIN-induced locomotor sedation in female mice. Conclusion Our findings suggest that genetic risk for schizophrenia can modulate the rewarding properties of the CB1 receptor agonist WIN and support the hypothesis that comorbidity between schizophrenia and cannabis use disorder may in part be driven by shared genetic risk factors.

Cannabidiol Modulates Brain Copper Homeostasis in Wild-Type-Like But Not Alzheimer’s Disease Transgenic Female Mice: Implications for Neuroprotective Therapy - Anthony Dosseto; Kaila Tonge; Tim Karl (Molecular Neurobiology, 2026)

Action spectrum of Bacillus subtilis spores for validation of polychromatic ultraviolet (UV) systems - Tim Schwarzenberger; Karl-Heinz Schön; Jutta Eggers; Saulius Nevas; Felix Schröppel; Kerstin Schwind; Peter Sperfeld (Water Research, 2025)

Knock-out of Tpm4.2/Actin Filaments Alters Neuronal Signaling, Neurite Outgrowth, and Behavioral Phenotypes in Mice - Sian Genoud; Chanchanok Chaichim; Rossana Rosa Porto; Tamara Tomanic; Holly Stefen; Esmeralda Paric; Soumalya Sarkar; Dasol Yoo; Wendi Gao; Edna C. Hardeman; Peter W. Gunning; Tim Karl; et al. (Molecular Neurobiology, 2025)
Tropomyosins (Tpm) are master regulators of actin dynamics through forming co-polymers with filamentous actin. Despite the well-understood function of muscle Tpms in the contractile apparatus of muscle cells, much less is known about the diverse physiological function of cytoplasmic Tpms in eukaryotic cells. Here, we investigated the role of the Tpm4.2 isoform in neuronal processes including signaling, neurite outgrowth, and receptor recycling using primary neurons from Tpm4.2 knock-out mice. Live imaging of calcium and electrophysiology data demonstrated increased frequency, yet reduced strength of single neuron spikes. Calcium imaging further showed an increase in neuronal networks. In vitro assays of Tpm4.2 knock-out neurons displayed impaired recycling of the AMPA neurotransmitter receptor subunit GluA1. Morphometric analysis of neurite growth showed increased dendritic complexity and altered dendritic spine morphology in Tpm4.2 knock-out primary neurons. Behavioral analysis of Tpm4.2 knock-out mice displayed heightened anxiety in the open field test, while the elevated plus maze displayed heightened anxiety only in females. Our study depicts the multi-faceted role of the Tpm4.2 isoform and its co-polymer F-actin population in neurons, with potential implications for better understanding diseases of the nervous system which involve actin cytoskeleton dysfunction.

Cxcl9-deficiency attenuates the progression of post-traumatic osteoarthritis in mice - Antonia Donat; Weixin Xie; Shan Jiang; Laura Janina Brylka; Thorsten Schinke; Tim Rolvien; Karl-Heinz Frosch; Anke Baranowsky; Johannes Keller (Inflammation Research, 2025)
Objective Osteoarthritis (OA) is one of the leading causes of disability in the aging population. While about 10% of the adult population is affected by OA, there is to date no curative treatment and joint replacement surgery remains the only option for treating end-stage OA. Previous studies found elevated levels of the chemokine C-X-C motif ligand 9 (CXCL9) in the synovial fluid of OA knees. However, the exact role of CXCL9 in OA progression is still unknown. Methods Female wild-type and Cxcl9 -deficient mice were challenged with a unilateral anterior cruciate ligament transection (ACLT). Joint destruction in early and late stages of experimental OA was assessed using micro-CT scanning, histological scoring, histomorphometry, and gene expression analysis. Results Inactivation of Cxcl9 protected from cartilage destruction and osteophyte formation in post-traumatic OA in mice. Similarly, indices of joint inflammation including synovitis and expression of pro-inflammatory interleukin-1beta were reduced in OA knees of Cxcl9 -deficient mice. However, bone erosion and pathophysiological changes in the subchondral bone compartment remained unaffected in Cxcl9 -deficient mice with experimental OA. Conclusion Our results point towards a pro-inflammatory role of CXCL9 in OA and identify a potential new target for the pharmacological treatment of OA.

Measurement of sawlog stacks on an individual log basis using LiDAR - Lukas Moik; Christoph Gollob; Tobias Ofner-Graff; Valentin Sarkleti; Tim Ritter; Andreas Tockner; Sarah Witzmann; Ralf Kraßnitzer; Karl Stampfer; Arne Nothdurft (Computers and Electronics in Agriculture, 2025)

Behavioural effects of oral cannabidiol (CBD) treatment in the superoxide dismutase 1 G93 A (SOD1G93 A) mouse model of amyotrophic lateral sclerosis - Sandip Ghimire; Fabian Kreilaus; Rossana Rosa Porto; Lyndsey L. Anderson; Justin J. Yerbury; Jonathon C. Arnold; Tim Karl (Psychopharmacology, 2025)
Background Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease affecting voluntary muscle movement as well as cognitive and other behavioural domains at later disease stages. No effective treatment for ALS is currently available. Elevated neuroinflammation, oxidative stress and alterations to the endocannabinoid system are evident in ALS. The phytocannabinoid cannabidiol (CBD) has anti-inflammatory and anti-oxidant properties. Thus, we evaluated the remedial effects of chronic oral cannabidiol (CBD) treatment on ALS-relevant behavioural domains in the copper-zinc superoxide dismutase 1 ( SOD1 ) mouse model of ALS that carries a G93A mutation ( SOD1 G93A ). Methods Male and female SOD1 G93A and wild type-like (WT) littermates were fed either a control (CHOW) or CBD-enriched chow diet (equivalent to a dose of 36 mg/kg per day) beginning from 10 weeks of age. Bodyweight and motor performance were recorded weekly from 11 to 19 weeks and open field behaviours at 12 and 18 weeks. Mice were also tested for prepulse inhibition (PPI), social behaviours, as well as fear-associated memory. Results CBD treatment ameliorated the bodyweight loss in female SOD1 G93A mice, tended to reinstate sociability in SOD1 G93A males, strengthened social recognition memory in SOD1 G93A females, and improved the PPI response in younger SOD1 G93A females at higher prepulse intensities. CBD had no effect on motor impairments but instead reversed the anxiolytic-like phenotype of 12-week-old male SOD1 G93A mice and decreased the acoustic startle response and strengthened cue freezing in male mice. Conclusion Thus, the current remedial oral dose of CBD delayed disease progression (inferred by bodyweight) in both male and female mice and improve specific cognitive deficits of SOD1 G93A mice in a sex specific manner without altering the motor phenotype.

The nematode signaling molecule ascr#18 induces prepenetration defenses in wheat against a leaf rust fungus - Akshita Kamboj; Jennifer Thielmann; Saba Delfan; Tim Kloppe; Philipp Schulz; Murli Manohar; Frank C. Schroeder; Daniel F. Klessig; Karl-Heinz Kogel (Journal of Plant Diseases and Protection, 2024)
Leaf rust, caused by the pathogenic biotrophic rust fungus Puccinia triticina ( Pt ), is one of the most destructive wheat diseases worldwide; its negative impact on crop yields is exacerbated by increasing temperatures due to climate change. Ascarosides are nematode pheromones that induce resistance to microbial pathogens and pests in a wide range of crops, making them valuable components in biocontrol scenarios. We investigated the effect on infection of various wheat ( Triticum aestivum ) genotypes with the virulent Pt race 77W × R by ascr#18, the major ascaroside secreted into the rhizosphere by plant-parasitic nematodes. Spraying the leaves with ascr#18 24 h before inoculation with fungal uredospores slowed disease development and resulted in a reduction of the number of rust pustules on treated compared to untreated leaves. Dose–response analysis over the nano- and micromolar range revealed a broad optimum concentration down to 0.01nM ascr#18. Microscopic analysis showed very early arrest of the fungus at the appressorial stage, with associated enhanced local accumulation of H 2 O 2 and abortive stoma penetration. Similarly, ascr#18 also induced strong resistance to Pt race PKTTS, confirming its race-unspecific biocontrol activity. The results of this study are consistent with and extend previous research that has shown that ascr#18 activates plant immunity and thus protects plants from pathogens even at very low doses.

Fish aggregations at oil and gas platform foundations in the North Sea - Bruno Ibanez‐Erquiaga; Henrik Baktoft; Tim Wilms; Tobias Karl Mildenberger; Jon Christian Svendsen (Fisheries Management and Ecology, 2024)
Globally, aging offshore oil and gas (O&G) platforms face resource depletion, and regulations often demand platform removal through decommissioning. In the North Sea, >€90 billion will be needed for decommissioning by 2060. However, the influence of O&G platforms on fish communities is poorly understood. This challenges predictions of possible fisheries scenarios associated with different decommissioning options. Here, we examined the role that North Sea platforms played on fish communities. We explored patterns of fish abundance and body size variation along transects from O&G platforms comparing catch per unit effort data. Fish abundance was positively associated with O&G platforms. Atlantic cod, plaice, saithe, and mackerel were most abundant near platforms. Similarly, larger Atlantic cod were near the O&G platforms. Our study provided information for decision‐making regarding platform decommissioning scenarios by evidencing O&G platform habitat provisioning for various commercial fish species.

A new foundation for the study of bird behaviour: Konrad Lorenz’s ‘Kumpan’ paper of 1935 - Tim Birkhead; Karl Schulze-Hagen (Journal of Ornithology, 2024)
The Nobel Prize in Physiology or Medicine was awarded to Konrad Lorenz, Niko Tinbergen and Karl von Frisch in 1973 for their pioneering work during the 1930s and 1940s, in the study of animal behaviour. Lorenz established the foundations of ethology in 1935 in what has become known as his “Kumpan paper”. The paper focussed on the social relationships between conspecifics (i.e. ‘kumpans’, companions) and provided a much-needed conceptual framework for the study of animal behaviour. We describe the origins and immediate reception of Lorenz’s paper using his correspondence with colleagues, mainly Erwin Stresemann who was then the influential editor of Journal für Ornithologie . The Kumpan paper was notable for its extraordinary originality, but also for its length and—in parts—its incomprehensible language. Most of Lorenz’s concepts were rapidly superseded as the field of Ethology/Animal Behaviour developed over the following decades. The paper (translated in full into English only in 1970) is rarely read today, but as we show, many of Lorenz’s observations of birds are both timeless and highly original and have the potential to inspire further research today.

Planning and licensing for marine aquaculture - Lynne Falconer; Karl Cutajar; Amalia Krupandan; Elisa Capuzzo; Richard A. Corner; Tim Ellis; Keith Jeffery; Eirik Mikkelsen; Heather Moore; Francis X. O'Beirn; Pauline O'Donohoe; Neil M. Ruane; et al. (Reviews in Aquaculture, 2023)
Marine aquaculture has the potential to increase its contribution to the global food system and provide valuable ecosystem services, but appropriate planning, licensing and regulation systems must be in place to enable sustainable development. At present, approaches vary considerably throughout the world, and several national and regional investigations have highlighted the need for reforms if marine aquaculture is to fulfil its potential. This article aims to map and evaluate the challenges of planning and licensing for growth of sustainable marine aquaculture. Despite the range of species, production systems and circumstances, this study found a number of common themes in the literature; complicated and fragmented approaches to planning and licensing, property rights and the licence to operate, competition for space and marine spatial planning, emerging species and diversifying marine aquaculture production (seaweed production, Integrated Multi‐Trophic Aquaculture [IMTA], nutrient and carbon offsetting with aquaculture, offshore aquaculture and co‐location and multiuse platforms), and the need to address knowledge gaps and use of decision‐support tools. Planning and licensing can be highly complicated, so the UK is used as a case study to show more detailed examples that highlight the range of challenges and uncertainty that industry, regulators and policymakers face across interacting jurisdictions. There are many complexities, but this study shows that many countries have undergone, or are undergoing, similar challenges, suggesting that lessons can be learned by sharing knowledge and experiences, even across different species and production systems, rather than having a more insular focus.

Biodiversity and environmental stressors along urban walking routes - Briony A. Norton; Meghann Mears; Philip H. Warren; Gavin M. Siriwardena; Kate E. Plummer; Tim Turner; Steven Hancock; Darren R. Grafius; Karl L. Evans (Urban Forestry & Urban Greening, 2023)

Impaired extinction of operant cocaine in a genetic mouse model of schizophrenia risk - Rose Chesworth; Gabriela Visini; Tim Karl (Psychopharmacology, 2023)
Background Individuals with schizophrenia have high rates of comorbid substance use problems. One potential explanation for this comorbidity is similar neuropathophysiology in substance use and schizophrenia, which may arise from shared genetic risk factors between the two disorders. Here we investigated if genetic risk for schizophrenia could affect drug reward and reinforcement for cocaine in an established mouse model of genetic risk for schizophrenia, the neuregulin 1 transmembrane domain heterozygous ( Nrg1 TM HET) mouse. Methods We examined drug-induced locomotor sensitization and conditioned place preference for several cocaine doses (5, 10, 20, 30 mg/kg) in male adult Nrg1 TM HET and wild-type-like (WT) littermates. We also investigated intravenous self-administration of and motivation for cocaine (doses 0.1, 0.5, 1 mg/kg/infusion), as well as extinction and cue-induced reinstatement of cocaine. In a follow-up experiment, we examined self-administration, extinction and cue-induced reinstatement of a natural reward, oral sucrose. Results Cocaine preference was similar between Nrg1 TM HET mice and WT littermates at all doses tested. Locomotor sensitization to cocaine was not affected by Nrg1 genotype at any dose. Although self-administration and motivation for cocaine was unaffected, extinction of cocaine self-administration was impaired in Nrg1 TM HET compared to WT controls, and cue-induced reinstatement was greater in Nrg1 mutants in the middle of the reinstatement session. Sucrose self-administration and extinction thereof was not affected by genotype, but inactive lever responding was elevated during cue-induced reinstatement for operant sucrose in Nrg1 TM HET mice compared to WTs. Discussion These results suggest impaired response inhibition for cocaine in Nrg1 TM HET mice and suggests Nrg1 mutation may contribute to behaviours which can limit control over cocaine use.

Correction to: Understanding the policy discourse within the formulation of the 2013 Indian National Food Security Act - Karl‑Axel Lindgren; Tim Lang (Food Security, 2022)

Understanding the policy discourse within the formulation of the 2013 Indian National Food Security Act - Karl-Axel Lindgren; Tim Lang (Food Security, 2022)
India was the third country in the world to enact into law a constitutional commitment to the right to food, following Brazil and South Africa. The 2013 National Food Security Act (NFSA) was the latest in a long line of post-Independence food policies aimed at tackling hunger. This paper explores the range of discourses among NFSA policy-makers, their views and disagreements, from drafting to the final Act. The research used mixed methods. Elite semi-structured interviews were conducted with 32 individuals who were either directly involved in NFSA formulation or food security specialist observers. Policy documents covering the period from before the Act and during the Act’s passage were critically analysed. Significant intra-governmental disagreements were apparent between two broad positions. A ‘pro-rights’ position sought to formulate a law that was as comprehensive and rights-based as possible, while a ‘pro-economy’ policy position saw the NFSA as a waste of money, resources and time, although recognising the political benefits of a food security law. These disagreements were consistent throughout the formulation of the NFSA, and in turn cast the Act as a product of compromise. Although there was broad consensus for a food security act, there was surprisingly little agreement exactly how that Act should look, what it should contain, and whom it should target. There was little consensus even on the right to food approach itself. The article contributes to the understanding of policy formulation in India specifically, and in developing countries in general, as well as to lend credence to the suitability of policy analysis to developing nations, otherwise normally grounded in Western traditions. The paper highlights a lack of cross-government cooperation in policy formulation, with the continued pressure of a short-term economic rationale undermining the policy goal of lessening hunger, despite some success.

Brain Reactions to Opening and Closing the Eyes: Salivary Cortisol and Functional Connectivity - Shen-Da Chang; Po-Chih Kuo; Karl Zilles; Tim Q. Duong; Simon B. Eickhoff; Andrew C. W. Huang; Arthur C. Tsai; Philip E. Cheng; Michelle Liou (Brain Topography, 2022)
This study empirically assessed the strength and duration of short-term effects induced by brain reactions to closing/opening the eyes on a few well-known resting-state networks. We also examined the association between these reactions and subjects’ cortisol levels. A total of 55 young adults underwent 8-min resting-state fMRI (rs-fMRI) scans under 4-min eyes-closed and 4-min eyes-open conditions. Saliva samples were collected from 25 of the 55 subjects before and after the fMRI sessions and assayed for cortisol levels. Our empirical results indicate that when the subjects were relaxed with their eyes closed, the effect of opening the eyes on conventional resting-state networks (e.g., default-mode, frontal-parietal, and saliency networks) lasted for roughly 60-s, during which we observed a short-term increase in activity in rs-fMRI time courses. Moreover, brain reactions to opening the eyes had a pronounced effect on time courses in the temporo-parietal lobes and limbic structures, both of which presented a prolonged decrease in activity. After controlling for demographic factors, we observed a significantly positive correlation between pre-scan cortisol levels and connectivity in the limbic structures under both conditions. Under the eyes-closed condition, the temporo-parietal lobes presented significant connectivity to limbic structures and a significantly positive correlation with pre-scan cortisol levels. Future research on rs-fMRI could consider the eyes-closed condition when probing resting-state connectivity and its neuroendocrine correlates, such as cortisol levels. It also appears that abrupt instructions to open the eyes while the subject is resting quietly with eyes closed could be used to probe brain reactivity to aversive stimuli in the ventral hippocampus and other limbic structures.

Characterisation of the Mouse Cerebellar Proteome in the GFAP-IL6 Model of Chronic Neuroinflammation - Rustam Asgarov; Monokesh K. Sen; Meena Mikhael; Tim Karl; Erika Gyengesi; David A. Mahns; Chandra S. Malladi; Gerald W. Münch (The Cerebellum, 2022)

Marine phytoplankton resilience may moderate oligotrophic ecosystem responses and biogeochemical feedbacks to climate change - Adam C. Martiny; George I. Hagstrom; Tim DeVries; Robert T. Letscher; Gregory L. Britten; Catherine A. Garcia; Eric Galbraith; David Karl; Simon A. Levin; Michael W. Lomas; Allison R. Moreno; David Talmy; et al. (Limnology and Oceanography, 2022)
Are the oceans turning into deserts? Rising temperature, increasing surface stratification, and decreasing vertical inputs of nutrients are expected to cause an expansion of warm, nutrient deplete ecosystems. Such an expansion is predicted to negatively affect a trio of key ocean biogeochemical features: phytoplankton biomass, primary productivity, and carbon export. However, phytoplankton communities are complex adaptive systems with immense diversity that could render them at least partially resilient to global changes. This can be illustrated by the biology of the Prochlorococcus “collective.” Adaptations to counter stress, use of alternative nutrient sources, and frugal resource allocation can allow Prochlorococcus to buffer climate‐driven changes in nutrient availability. In contrast, cell physiology is more sensitive to temperature changes. Here, we argue that biogeochemical models need to consider the adaptive potential of diverse phytoplankton communities. However, a full understanding of phytoplankton resilience to future ocean changes is hampered by a lack of global biogeographic observations to test theories. We propose that the resilience may in fact be greater in oligotrophic waters than currently considered with implications for future predictions of phytoplankton biomass, primary productivity, and carbon export.

Assessment of sleep quality and daytime sleepiness in German national ice hockey players preparing for the world championship - Annika Hof zum Berge; Fabian Loch; Karl Schwarzenbrunner; Alexander Ferrauti; Tim Meyer; Mark Pfeiffer; Michael Kellmann (German Journal of Exercise and Sport Research, 2021)
Objectives Objectives were to examine subjective sleep quality and daytime sleepiness of the German ice hockey junior national team prior to the world championship to identify athletes of concern and areas of optimization with the intention of equally preventing injury and enhancing performance. Methods Twenty-one athletes ( M age = 18.5 ± 0.6 years, M height = 181.7 ± 4.3 cm, M weight = 81.4 ± 7.1 kg), playing for national ( n = 13) and international ( n = 8) home clubs, answered the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS) before training camp (T1, day 1) and prior to tournament (T2, day 11). Results Overall, 9 players at T1 and 7 at T2 were identified as bad sleepers (PSQI > 5), while high sleepiness (ESS > 10) was found for 6 athletes at each measurement time. Group means and standard deviations reduced descriptively for PSQI (T1 = 5.38 ± 2.31, T2 = 4.57 ± 2.36) and ESS (T1 = 9.24 ± 3.74, T2 = 8.48 ± 3.28). Tendential differences were visible for PSQI in international-based players (Z = −1.7, p = 0.09) and ESS in first-national-league players (Z = −1.73, p = 0.08) over time. Higher PSQI values for international-based players (6.25 ± 2.6) were found compared to first-national-league (5.83 ± 1.60) and lower-league players (4.00 ± 2.08), with large effect sizes for lower-league compared to international ( d = 0.95) and national players ( d = 0.98) at T1 and small effect sizes compared to first-league players ( d = 0.24) at T2. Conclusion Findings emphasize great vulnerability and individuality and underline the importance of intraindividual sleep monitoring to meet the requirements needed to equally obtain health and enhance overall performance.

Upregulation of Proteolytic Pathways and Altered Protein Biosynthesis Underlie Retinal Pathology in a Mouse Model of Alzheimer’s Disease - Mehdi Mirzaei; Kanishka Pushpitha; Liting Deng; Nitin Chitranshi; Veer Gupta; Rashi Rajput; Abu Bakr Mangani; Yogita Dheer; Angela Godinez; Matthew J. McKay; Karthik Kamath; Dana Pascovici; et al. (Molecular Neurobiology, 2019)

Changes in the spatial patterns of human appropriation of net primary production (HANPP) in Europe 1990–2006 - Christoph Plutzar; Christine Kroisleitner; Helmut Haberl; Tamara Fetzel; Claudia Bulgheroni; Tim Beringer; Patrick Hostert; Thomas Kastner; Tobias Kuemmerle; Christian Lauk; Christian Levers; Marcus Lindner; et al. (Regional Environmental Change, 2016)

Paths to a sustainable food sector: integrated design and LCA of future food supply chains: the case of pork production in Sweden - Ulf Gunnar Sonesson; Katarina Lorentzon; Annica Andersson; Ulla-Karin Barr; Jan Bertilsson; Elisabeth Borch; Carl Brunius; Margareta Emanuelsson; Leif Göransson; Stefan Gunnarsson; Lars Hamberg; Anna Hessle; et al. (The International Journal of Life Cycle Assessment, 2016)

Development of a new downscaling method for hydrologic assessment of climate change impacts in data scarce regions and its application in the Western Ghats, India - Paul D. Wagner; Tim G. Reichenau; Shamita Kumar; Karl Schneider (Regional Environmental Change, 2015)

Obesity and head and neck cancer risk and survival by human papillomavirus serology - Xinmiao Tan; Heather H. Nelson; Scott M. Langevin; Michael McClean; Carmen J. Marsit; Tim Waterboer; Michael Pawlita; Karl T. Kelsey; Dominique S. Michaud (Cancer Causes & Control, 2015)

Chronic cannabidiol treatment improves social and object recognition in double transgenic APPswe/PS1∆E9 mice - David Cheng; Jac Kee Low; Warren Logge; Brett Garner; Tim Karl (Psychopharmacology, 2014)

Integrated Modeling of Global Change Impacts on Agriculture and Groundwater Resources - Roland Barthel; Tim G. Reichenau; Tatjana Krimly; Stephan Dabbert; Karl Schneider; Wolfram Mauser (Water Resources Management, 2012)

Differential Transcript Expression of Wall-loosening Candidates in Leaves of Maize Cultivars Differing in Salt Resistance - Christoph-Martin Geilfus; Christian Zörb; Christina Neuhaus; Tim Hansen; Hartwig Lüthen; Karl H. Mühling (Journal of Plant Growth Regulation, 2011)

Folgen des Globalen Wandels für das Grundwasser in Süddeutschland – Teil 1: Naturräumliche Aspekte - Roland Barthel; Tim G. Reichenau; Markus Muerth; Christoph Heinzeller; Karl Schneider; Rolf Hennicker; Wolfram Mauser (Grundwasser, 2011)

Cannabidiol potentiates Δ9-tetrahydrocannabinol (THC) behavioural effects and alters THC pharmacokinetics during acute and chronic treatment in adolescent rats - Charlotte Klein; Emily Karanges; Adena Spiro; Alexander Wong; Jarrah Spencer; Thanh Huynh; Nathan Gunasekaran; Tim Karl; Leonora E. Long; Xu-Feng Huang; Kelly Liu; Jonathon C. Arnold; et al. (Psychopharmacology, 2011)

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

A follow-up study: acute behavioural effects of Δ9-THC in female heterozygous Neuregulin 1 transmembrane domain mutant mice - Leonora E. Long; Rose Chesworth; Jonathon C. Arnold; Tim Karl (Psychopharmacology, 2010)

The biogeography of avian extinctions on oceanic islands revisited - Tim M. Blackburn; Phillip Cassey; Karl L. Evans; Kevin J. Gaston; Richard P. Duncan (Journal of Biogeography, 2009)
A recent paper by Karels et al ., ‘The biogeography of avian extinctions on oceanic islands’ ( Journal of Biogeography , 2008, 35 , 1106–1111), uses structural equation modelling to assess the causes of the number of island bird species driven extinct in the historical period. Here, we critically assess the conclusions of the paper and argue that it does not provide the new insights into the causes of extinction in island birds that its authors claim.

Reproductive biology of the European Cuckoo Cuculus canorus: early insights, persistent errors and the acquisition of knowledge - Karl Schulze-Hagen; Bard G. Stokke; Tim R. Birkhead (Journal of Ornithology, 2009)

Threats to Avifauna on Oceanic Islands Revisited - TIM M. BLACKBURN; PHILLIP CASSEY; RICHARD P. DUNCAN; KARL L. EVANS; KEVIN J. GASTON (Conservation Biology, 2008)

Effect of Src kinase inhibition on metastasis and tumor angiogenesis in human pancreatic cancer - Ivan Ischenko; Markus Guba; Maksim Yezhelyev; Armine Papyan; Gerald Schmid; Tim Green; Michael Fennell; Karl-Walter Jauch; Christiane J. Bruns (Angiogenesis, 2007)

Body mass estimations for Plateosaurus engelhardti using laser scanning and 3D reconstruction methods - Hanns-Christian Gunga; Tim Suthau; Anke Bellmann; Andreas Friedrich; Thomas Schwanebeck; Stefan Stoinski; Tobias Trippel; Karl Kirsch; Olaf Hellwich (The Science of Nature, 2007)

In situ dark field microscopy for on-line monitoring of yeast cultures - Ning Wei; Jia You; Karl Friehs; Erwin Flaschel; Tim Wilhelm Nattkemper (Biotechnology Letters, 2007)

Anaerobic Degradation and Transformation of p -Toluidine by the Sulfate-Reducing Bacterium Desulfobacula toluolica - Tim Raber; Thomas Gorontzy; Magarete Kleinschmidt; Klaus Steinbach; Karl-Heinz Blotevogel (Current Microbiology, 1998)

Identification of a modifier gene locus on chromosome 1p35-36 in familial adenomatous polyposis - Zuzana Dobbie; Karl Heinimann; D. Tim Bishop; Hansjakob Müller; R. J. Scott (Human Genetics, 1997)